2000
DOI: 10.1021/jp992248k
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Studies of Ternary Systems:  I. LiCl−(n-Bu)4NCl−H2O at 25 °C

Abstract: Osmotic coefficients were determined for the ternary system lithium chloride−tetra-n-butylammonium chloride−water over a wide range of concentrations and ionic strength fractions at 25 °C by utilizing a gravimetric isopiestic technique. The mean ionic activity coefficients were calculated using the Scatchard−Rush−Johnson equations. Using the theories developed by Friedman and by Leifer and Wigent, the excess free energy, Friedman's interaction parameters, and contributions due to pairwise, triplet, and quadrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Very recently, Fox and Leifer have employed the Scatchard−Rush−Johnson (SRJ) equations to analyze the osmotic coefficient data of the LiCl−( n -Bu) 4 NCl−H 2 O system up to I = 8 mol kg -1 . These authors have successfully determined various interaction terms using the theories of Friedman and of Leifer and Wigent .…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Fox and Leifer have employed the Scatchard−Rush−Johnson (SRJ) equations to analyze the osmotic coefficient data of the LiCl−( n -Bu) 4 NCl−H 2 O system up to I = 8 mol kg -1 . These authors have successfully determined various interaction terms using the theories of Friedman and of Leifer and Wigent .…”
Section: Resultsmentioning
confidence: 99%
“…It is hoped that the estimation of the ionic-interactions shown above will find its application in understanding the origin of forces responsible for the effects of ions on reactions of organic and biological interest. The osmotic and activity coefficient data of the above mixtures can also be successfully analyzed by the equations of Scatchard et al to obtain information on ionic interactions as shown by Leifler and Wigent and Fox and Leifler …”
Section: Discussionmentioning
confidence: 99%
“…In a significant work, Fox and Leifer have recently demonstrated presence of binary, ternary, and higher order interactions in the mixtures of clathrate-forming TBAC with LiCl. 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation